Students' lived experiences of formulating a research project - Joorst, J. (South African Journal of Higher Education, 2026)
Stellenbosch University aims to be a leading research-focused institution in Africa and a globally recognised hub for inclusivity and innovation by 2040. The university emphasises high-quality academic offerings, including Teaching, Learning, and Assessment (TLA) practices. This study focuses on Bachelor of Education Honours (B.Ed. Hons) students' experiences with an Introduction to Research Methods module, specifically on the formulation of research projects. This focus is important for research because the quality of students’ preparation and development at honours level influences these students’ throughput rates and overall preparedness for master’s and PhD studies. The data from semi-structured interviews revealed that despite different supervision approaches across two universities, students have similar challenges, but agentic capacities no less. The findings of the study offer insights for module redesign and postgraduate student success.